KONDISI NUTRIEN DAN KELIMPAHAN PLANKTON DI LINGKUNGAN PERAIRAN TAMBAK PILOT PROJECT WWF INDONESIA, KELURAHAN KARANG ANYAR PANTAI KOTA TARAKAN PROPINSI KALIMANTAN UTARA - Wiharyanto, Dhimas; Santosa, Mohammad Budi (Jurnal Harpodon Borneo, 2013)
The availability of natural food in the waters affected by internal condition that isnutrient content. With sufficient nutrients will be able to support the growth ofphytoplankton which in turn form the food chain as part of the ecological chain events in it. Brackish water pond is one of human making ecosystem. Commonly, It’s use for fisheries production especially shrimp or fishes purporting. In Coastal of North Kalimantan, to running its have been used traditional system. This system is depending to the natural condition. The Available of nutrients and plankton condition are important thing for supporting life in the waters column and for management system brackish water pond. Thus, changes in the content of nutrients and plankton in the environment and in the brackish water pond becomes very necessary to be known. This study aims to determine the condition of nutrient content and plankton in the pond waters environtment. Nitrate concentrations in the pond water was found ranged from 0.0004 to 0.309 ppm, while in the waters of the river / outlets ranging from 0.012 to 0.243 ppm. The phosphate concentration in the pond water obtained in this study ranged from 0.001 to 0.741 ppm, while in the waters of the river ranges from 0019 to 0.067 ppm. In generally, nutrient concentration range obtained is still support for the life of plankton in the brackish water pond.Key words: nutrients, nitrat, fosfat, plankton, brackish water ponds.